Application of the Mind Map Model to Improve Students' Understanding of Indonesian Ethnic and Cultural Diversity Material - Pratama, Raka Nurmawan; Sujana, Atep; Agustin, Mubiar (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
The problem in this research is the students' lack of understanding about the material of Indonesian ethnic and cultural diversity. This is caused by the use of the social studies learning model being less able to generate student motivation. This research was conducted in the fifth grade of SDN Babakan Bandung Tanjungsari, Sumedang Regency, totaling 33 students. The model in this study uses the Kemmis and Mc Taggart classroom action research model. This research was conducted in two cycles. Each cycle consists of one learning and four stages, planning, implementation, observation, and reflection. The research instruments used were observation sheets, field notes, documentation, assessment guidelines, and interview sheets. Data analysis techniques used are qualitative data analysis techniques and quantitative data. Based on the research that has been done in the first cycle the average value of student understanding is 69, in the second cycle, it increases to 80. These results indicate that the mind map model can improve students' understanding of the material on ethnic and cultural diversity in Indonesia.